Agile Strategy - Fernando, Ralph (Pearson Education, Limited, 2019)
Ralph Fernando is a business leader, consultant and writer. He draws together strategy, operations and technology experience earned on an international stage, where he focuses on value creation in private, public and voluntary organisations. Ralph recognises that the boundaries between functional disciplines are far blurrier in real life than many would have you believe, and that true agility lies in how they interact. He is driven by the need to make this agility a practical, commercial reality within organisations, after ten years of hearing leading thinkers and executives talk a good game about it. A Cambridge graduate and Warwick Business School MBA, in his spare time Ralph enjoys just spending time with his wife, Marielle, and their two boys Lucas and Aaron, as well as writing and recording songs at his home studio.